2010
DOI: 10.1016/j.cell.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Histone Replacement by SWR1 Requires Dual Activation with Histone H2A.Z and Canonical Nucleosome

Abstract: Histone variant H2A.Z-containing nucleosomes are incorporated at most eukaryotic promoters. This incorporation is mediated by the conserved SWR1 complex, which replaces histone H2A in canonical nucleosomes with H2A.Z in an ATP-dependent manner. Here, we show that promoter-proximal nucleosomes are highly heterogeneous for H2A.Z in Saccharomyces cerevisiae, with substantial representation of nucleosomes containing one, two, or zero H2A.Z molecules. SWR1-catalyzed H2A.Z replacement in vitro occurs in a stepwise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
242
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(276 citation statements)
references
References 61 publications
33
242
1
Order By: Relevance
“…It is possible that sonication caused loss of poorly cross-linked nucleosomes, and differences in the degree of cross-linking of different histones (8) might have resulted in discrepant ChIP efficiencies between them. The excellent concordance between our study using native chromatin and that of Luk et al (35) using cross-linked chromatin confirms that H2A is as abundant over centromeres as it is over the entire genome, as expected for a centromeric particle containing all four histones. Our findings are consistent with a report that the Mif2 kinetochore-specific protein coimmunopurifies with Cse4, H4, H2A, and H2B, but not detectably to H3, when purified without cross-linking or enzymatic DNA fragmentation (36).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is possible that sonication caused loss of poorly cross-linked nucleosomes, and differences in the degree of cross-linking of different histones (8) might have resulted in discrepant ChIP efficiencies between them. The excellent concordance between our study using native chromatin and that of Luk et al (35) using cross-linked chromatin confirms that H2A is as abundant over centromeres as it is over the entire genome, as expected for a centromeric particle containing all four histones. Our findings are consistent with a report that the Mif2 kinetochore-specific protein coimmunopurifies with Cse4, H4, H2A, and H2B, but not detectably to H3, when purified without cross-linking or enzymatic DNA fragmentation (36).…”
Section: Discussionsupporting
confidence: 89%
“…Our native ChIP-seq analysis also showed that H2A is present at all 16 yeast centromeres at the same level as over the rest of the genome. We confirmed this result by analyzing X-ChIP data from a published study (35). Because that study was performed on formaldehyde cross-linked chromatin by the same laboratory that previously reported deficiency of H2A over centromeres (28), we might attribute the different outcomes to the use of sonication in the first study to fragment and solubilize DNA, versus the use of MNase in the second study (35).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Notably, H2A.Z levels increased within the next 10 h (Fig. 2E), consistent with replication-independent assembly (Luk et al 2010;Nekrasov et al 2012). Altogether, our data demonstrate that histone variants are not recycled with similar efficiency at replication forks and that H2A.Z marked sites may not be maintained after DNA replication.…”
Section: H2az Domains Are Challenged By the Passage Of Replication Fsupporting
confidence: 77%
“…Histone H2A.Z is itself subject to posttranslational modifications, including acetylation, ubiquitylation, and sumoylation, and these may alter its chromatin association, exchange dynamics, structure, and function (8,32,39,41,43,66,81,84,95). H2A.Z is broadly but nonuniformly distributed throughout the chromosomes and is deposited by specific remodeling complexes, such as the yeast SWR1 complex (SWR1) (3,45,51,60,67).…”
mentioning
confidence: 99%